(untitled) (Edma 0-6: Educación Matemática en la Infancia, 2021)
This time it’s the turn of a cartoon series in which mathematics are present, but within what is known as STEM. We introduce Blaze and the Monster Machines, in which some trucks, with the help of two human characters and a helmet of augmented reality, solve problems with the help of mathematics, science and technology. We describe roughly this production and we focus on the most explicit mathematical contents: measurement throughout the first season, where extensive and intensive magnitudes appear; and the angles.